Penggunaan Model Aritmatik dan Geometrik dalam Laju Pertumbuhan Penduduk di Kota Medan pada Tahun 2029 - Syahfitri, Sella; Deasy, Deasy; Sugarda, Ahmad; Aprilia, Rima (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Population growth is an important issue for the country in Indonesia because a significant increase in population growth can lead to a lack of housing for the growing population. This study aims to determine the rate of population growth in the city of Medan by using arithmetic and geometric models to find the results of calculations of the population of the city of Medan in the next 10 years based on standard deviations and correlation coefficients. The use of the arithmetic (linear) model for population growth increases constantly and is not seen from the number of previous populations, while the geometric (exponential) model assumes the number of people seen from how large the previous population is, then the growth every year will be rapid (not fixed). The results show that the geometric model has the smallest standard deviation value of 61,320,657 compared to the arithmetic model with the largest standard deviation value of 61,321,357. It can be concluded that the geometric model is used in calculating the population growth rate of the city of Medan in 2029 because the geometric model has the smallest standard deviation which produces the population in 2020 of 2,301,101 people and in 2029 of 2,501,069